PENGARUH KUALITAS DAN INOVASI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK BATRISYIA DENGAN VARIABEL INTERVENING MINAT BELI - Nirma, Nirma; Welsa, Henny; Hutami, Lusia Tria Hatmanti (STKIP Persada Khatulistiwa Sintang, 2023)
The evolution of contemporary market conditions has had numerous significant impacts on the cosmetics sector, particularly Indonesia. The cosmetics sector has seen economic and socio-cultural advancement, as well as changes in lifestyle, resulting in the emergence of a wide variety of beauty products. The purpose of this study is to identify the elements that influence purchase decisions for Batrisyia Herbal Beauty Products in Yogyakarta. This study employs quantitative research methods, with a population of 100 Batrisyia product users serving as the research sample. The research data is based on primary data gathered via a questionnaire. Data Quality Test employs validity and reliability tests. Data Analysis Methods Using Classical Assumption Tests and Multiple Linear Regression Analysis. In this study, the F and t tests, coefficient of determination tests, and Sobel tests were used. Based on the results of the data analysis, Product quality positively and significantly influences purchasing interest; Product innovation does not significantly affect purchasing interest; Product quality positively and significantly influences purchasing decisions; Product interest positively and significantly influences purchasing decisions